Занурення, як найприродніший спосіб вивчення мови - Горбач , Натапія; Кальченко, Тетяна (Colloquium-journal Warszawa, Polska, 2023)
Приводяться різні дефініції метода занурення та розглядається історія появу даного методу. В роботі дається оцінка метода Берліца, який все ще залишається найефективнішим способом вивчення мови і продовжує використовуватися сьогодні, тому розглядаються ключові елементи цього методу. Також розглядаються переваги та недоліки двомовності та занурення. Автори статті діляться власним досвідом створення англомовного середовища.

Various definitions of the immersion method are given and the history of the emergence of this method is considered. The work evaluates the Berlitz method, which still remains the most effective method of language learning and continues to be used today, so the key elements of this method are reviewed. The advantages and disadvantages of bilingualism and immersion are also discussed. The authors of the article share their own experience of creating an English-speaking environment.
Keywords: метод занурення, найефективніший спосіб вивчення мови, ключові елементи недоліки, англомовне середовище; immersion method, the most effective way of learning the language, key elements, disadvantages, English-speaking environment